High magnetic field test of bismuth Hall sensors for ITER steady state magnetic diagnostic - Ďuran, I; Entler, S; Kohout, M; Kočan, M; Vayakis, G (The Review of scientific instruments, 2016)
Performance of bismuth Hall sensors developed for the ITER steady state magnetic diagnostic was investigated for high magnetic fields in the range ±7 T. Response of the sensors to the magnetic field was found to be nonlinear particularly within the range ±1 T. Significant contribution of the planar Hall effect to the sensors output voltage causing undesirable cross field sensitivity was identified. It was demonstrated that this effect can be minimized by the optimization of the sensor geometry and alignment with the magnetic field and by the application of "current-spinning technique."